TINJAUAN YURIDIS TERHADAP PENYELESAIAN KREDIT MACET MELALUI PENJUALAN DI BAWAH TANGAN ATAS OBJEK JAMINAN YANG DIIKAT DENGAN FIDUSIA PADA BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG SAMARINDA KCP UNIT SUNGAI PINANG DALAM - Wirna Aprilia (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT The main activity of the bank as an intermediary is to channel credit to the community by making credit agreements. The need for funds generally in the Indonesian banking world is called credit, sometimes associated with the guarantee of securing funds or credit itself. Credit is the largest part of the source of income for the Bank because loans given selectively and directed by banks to customers can support the implementation of development so that it is beneficial for the welfare of the community. Loans provided by banks as a means to encourage economic growth both in general and specifically for certain sectors.This research is normative legal research, namely legal research methods carried out by examining library materials or mere secondary data. The research procedure that is used is legal material collection research that will be used in this research is a literature study, namely data collection by reading the laws and regulations, official documents, and literature that are closely related to the issues discussed.From the results of research that have been carried out and analyzed by the Settlement in Overcoming the Inhibiting Factors of Bad Credit Through Under-the-Sale Sales of Objects Guaranteed Tied to Fiduciary by way of Notification of late payments, Giving warning letters and Submissions through the District Court. The causes of credit arrears that result in non-performing loans, namely the existence of internal bank factors, inhibited debtor business activities, use of credit deviations, and the existence of bad faith from debtors and legal protection for creditors in the settlement of bad loans through under-the-sale sales of guaranteed objects Fiduciary Keywords: Bank, Credit, and Loss